Complications in treatment gastroduodenal ulcer surgery - Piacenza, Guillermo; Czarnevicz, Daniel; Ferreira, Carlos (Cirugía del Uruguay, 1994)
The treatment of gastroduodenal peptic ulcus (GDPU) has undergone different stages with /he aim of improving results and decreasing morbimortality. The authors make a retrospective study of 1.200 cases of GDPU surgery (from 1980 to 1989) in arder to analyse the reality of the treatment of this disease in our environment. Global morbility was 28,8%, this was higher in urgent surgery, as expected. The most frequent complica/ion were infections (7,9%) followed by post-operative digestive haemorrhage (4, 1%); suture failure, although infrequent, presented 23% mortality. Ulcer recidive presented a low incidence (6,6%) when co.'71pared to o/her series as well as functional disturbances (1 %). Global mortality was 2,5%, increasing with age, and it was 5 times higher in urgent /han elective surgery.